2020
DOI: 10.1186/s12859-020-3398-9
|View full text |Cite
|
Sign up to set email alerts
|

Analyses on clustering of the conserved residues at protein-RNA interfaces and its application in binding site identification

Abstract: Background: The maintenance of protein structural stability requires the cooperativity among spatially neighboring residues. Previous studies have shown that conserved residues tend to occur clustered together within enzyme active sites and protein-protein/DNA interfaces. It is possible that conserved residues form one or more local clusters in protein tertiary structures as it can facilitate the formation of functional motifs. In this work, we systematically investigate the spatial distributions of conserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…To identify sequences with well-clustered aromatic residues and motivated by Yang et al, we applied a metric that computes the average inverse distance among aromatic residues, which we term aromatic clustering (Figure 2C; see Methods). 106 Of relevance to our application, this parameter is robust in the limit of small fractions of aromatic with the fraction of aromatic or aliphatic residues (x-axis). Among those of X. laevis PLDs, the clustering score Velo1 PLD (black diamond) is higher than all but one, and among those of the PLDs from PhaseSepDB, the clustering score is higher than all but two.…”
Section: ■ Resultsmentioning
confidence: 99%
“…To identify sequences with well-clustered aromatic residues and motivated by Yang et al, we applied a metric that computes the average inverse distance among aromatic residues, which we term aromatic clustering (Figure 2C; see Methods). 106 Of relevance to our application, this parameter is robust in the limit of small fractions of aromatic with the fraction of aromatic or aliphatic residues (x-axis). Among those of X. laevis PLDs, the clustering score Velo1 PLD (black diamond) is higher than all but one, and among those of the PLDs from PhaseSepDB, the clustering score is higher than all but two.…”
Section: ■ Resultsmentioning
confidence: 99%
“…We measured clustering of particular residue classes (e.g., positive, negative, and aromatic residues) within FRQ's sequence by calculating the average inverse weighted distance (IWD). The IWD is defined as: where S is the set of target residue positions, Si is the i-th element of S, NS is the number of items in S, and Npairs is the number of pairwise combinations between elements of S (Schueler-Furman and Baker, 2003;Yang et al, 2020). The IWD was then compared to the IWD calculated from 10,000 randomly shuffled FRQ sequences to assess significance as IWD values above the 95 percentile, and following the approach presented in (Cohan et al, 2021) we calculated a residue class specific Z-score to allow comparisons across orthologs that differ in length and amino acid composition.…”
Section: Sequence Analysismentioning
confidence: 99%
“…This tendency holds true for protein–protein/nucleic acid interactions 11,12 . The higher packing density of conserved residues at interfaces and within enzyme active sites may suggest their cooperativity in function exertion 10 . That the conserved residues form one or more localized clusters within interfaces or tertiary structures will facilitate the formation of some “functional motifs.” Thus, based on the above, we think the PSSM profile encoded in a form of spatial neighbors can better reflect the evolutionary characteristics of interface conserved residues than that encoded in a form of sequence neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al utilized sequence and structure characteristics encoded in a structural window to predict RNA‐binding residues 9 . Studies have shown the conserved interface residues often occur clustered together in tertiary structures 10 . This tendency holds true for protein–protein/nucleic acid interactions 11,12 .…”
Section: Introductionmentioning
confidence: 99%